THE ROLE OF ASEAN AS AN INTERNATIONAL ORGANIZATION IN RESOLVING THE DISPUTES IN THE SOUTH OF CHINA SEA - Muhammad Rafi Darajati (Progressive Law Review, 2022)
As an international organization, the Association of Southeast Asian Nations (ASEAN) must be responsible for maintaining and maintaining peace and security in Southeast Asia. One exciting development regarding regional security in Southeast Asia today is the issue of the South China Sea dispute. By law, the Philippines has brought the dispute to the Permanent Court of Arbitration (PCA). The verdict from the PCA said that China's claims regarding the nine-dash lines were indisputable and had no legal basis. However, China rejects the ruling and remains aggressive in the South China Sea, potentially creating regional instability. This article aims to look at the role of ASEAN in resolving a dispute that occurs in the South China Sea. This article argues that in dispute in the South China Sea, ASEAN plays a role as an intermediary for countries joined in ASEAN with China in diplomatic dialogue and resolves and ensures the implementation of the Code of Conduct in the South China Sea so that disputes do not extend to military conflict so peace and security in the southern China sea region can be achieved.